2020
DOI: 10.3390/brainsci10110857
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Spinal Cord in Multiple Sclerosis: Past, Present, Future

Abstract: Spinal cord imaging in multiple sclerosis (MS) plays a significant role in diagnosing and tracking disease progression. The spinal cord is one of four key areas of the central nervous system where documenting the dissemination in space in the McDonald criteria for diagnosing MS. Spinal cord lesion load and the severity of cord atrophy are believed to be more relevant to disability than white matter lesions in the brain in different phenotypes of MS. Axonal loss contributes to spinal cord atrophy in MS and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 126 publications
0
18
0
2
Order By: Relevance
“…Multiple sclerosis (MS) is an inflammatory demyelinating disease affecting both the brain and the spinal cord [1,2]. MS is the most frequent cause of disability in the young and middle-aged population in developed countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an inflammatory demyelinating disease affecting both the brain and the spinal cord [1,2]. MS is the most frequent cause of disability in the young and middle-aged population in developed countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Also, T2 lesion detection in the spinal cord can be challenging, especially for small and lateral cord lesions due to partial volume effects. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…1 Demyelination, axonal loss, and gliosis contribute to damage of this region, resulting in chronic motor, sensory, and autonomic dysfunction. 1,2 Spinal cord atrophy, especially in the cervical segment, occurs to a variable extent in both relapsing-remitting (RR) and progressive (P) MS, 1,3,4 and is often associated with clinical disability. 1,[3][4][5] Longitudinal studies have consistently demonstrated that spinal cord atrophy progresses over time in all disease phenotypes.…”
mentioning
confidence: 99%
“…1,2 Spinal cord atrophy, especially in the cervical segment, occurs to a variable extent in both relapsing-remitting (RR) and progressive (P) MS, 1,3,4 and is often associated with clinical disability. 1,[3][4][5] Longitudinal studies have consistently demonstrated that spinal cord atrophy progresses over time in all disease phenotypes. [6][7][8][9][10][11][12] Because of its strong correlation with clinical disability and short-term disease worsening, 8,9 cervical cord atrophy progression appears to be a good candidate biomarker for monitoring disease evolution, and may be included as an outcome measure for clinical trials.…”
mentioning
confidence: 99%